2020
DOI: 10.3389/fonc.2020.01361
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anticancer Effect of a Combination of S-adenosylmethionine (SAM) and Immune Checkpoint Inhibitor (ICPi) in a Syngeneic Mouse Model of Advanced Melanoma

Abstract: Immune checkpoint inhibitors (ICPi) targeting the PD-1/PD-L1 pathway have shown marked success in patients with advanced melanoma. However, 60–70% of patients fail to respond, warranting a therapeutic intervention that could increase response rates. We and others have shown that S-adenosylmethionine (SAM), a universal methyl donor, has significant anticancer effects in numerous cancers previously; however, its effect on melanoma progression has not been evaluated. Interestingly, SAM was reported to be essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Indeed, in preclinical models, the N1-acetylspermidine precursor, spermidine, has marked anti-inflammatory and immunostimulatory effects 24 – 27 . Administration of S-adenosylmethionine attenuates the cytokine storm induced by bacterial sepsis 28 and mediates immunostimulatory effects in a cancer model 29 . Clinical trials have demonstrated that taurine, the downstream metabolite of hypotaurine, decreases serum markers of inflammation including C-reactive protein 30 , which is a negative prognostic marker of COVID-19 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in preclinical models, the N1-acetylspermidine precursor, spermidine, has marked anti-inflammatory and immunostimulatory effects 24 – 27 . Administration of S-adenosylmethionine attenuates the cytokine storm induced by bacterial sepsis 28 and mediates immunostimulatory effects in a cancer model 29 . Clinical trials have demonstrated that taurine, the downstream metabolite of hypotaurine, decreases serum markers of inflammation including C-reactive protein 30 , which is a negative prognostic marker of COVID-19 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This makes CD8+ T cells non-functional and unresponsive to ICPi [ 175 ]. Indeed, we showed that SAM in combination with ICPi (anti-PD-1) significantly reduced tumor volume and weight compared to monotherapy in a syngeneic mouse model of advanced melanoma [ 177 ]. This effect was partially due to the elevated activation, proliferation, and cytokine production of CD8 T cells.…”
Section: Targeting Methylation In the Treatment Of Human Diseasementioning
confidence: 99%
“…In our study, there was no observed synergistic effect between STAT3 inhibitor Stattic and anti-PD-1. Former research showed that the effect of combination treatment containing anti-PD-1 therapy on melanoma was not significant in the short term when compared to anti-PD-1 alone after tumor formation for 14 days (46). Another study focused on the antitumor activity of combinations of cytotoxic chemotherapy and immune checkpoint inhibitors of various mouse models.…”
Section: Discussionmentioning
confidence: 99%